1979
DOI: 10.1136/bmj.1.6174.1323-a
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of nausea and vomiting with cytotoxic chemotherapy: a prospective randomised trial of antiemetics.

Abstract: 1323and still be labelled "approximately 141 mmol/l" and comply with the BPC standard. Another variant of Difusor is stated to contain approximately 130 mmol/l of sodium, and a 5% variation would allow a range of 123-5 to 136-5 mmol/l.The BPC limits for sodium content of haemodialysis solutions are ±3%, and the manufacturers of our haemodialysis solutions work to limits of ±3 mmol/l, which is equivalent to 2-16% on a sodium content of 139 mmol/l. We appreciate the difficulties encountered in manufacturing to n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(38 citation statements)
references
References 1 publication
0
37
1
Order By: Relevance
“…With the development of national and international guidelines, the focus shifted from treatment to prevention through antiemetic prophylaxis [18]. Although CINV remains a concern, studies have shown that whereas the overall incidence of CINV was 83 percent in 1979 [19], the incidence of acute nausea was 35 percent just 25 years later [20]. The pharmaceutical industry's successful efforts had a profound impact on patients' quality of life and allowed many patients to complete chemotherapy regimens who previously would not have been able to do so [17].…”
Section: Potential Funding Sources For Mental Health Researchmentioning
confidence: 99%
“…With the development of national and international guidelines, the focus shifted from treatment to prevention through antiemetic prophylaxis [18]. Although CINV remains a concern, studies have shown that whereas the overall incidence of CINV was 83 percent in 1979 [19], the incidence of acute nausea was 35 percent just 25 years later [20]. The pharmaceutical industry's successful efforts had a profound impact on patients' quality of life and allowed many patients to complete chemotherapy regimens who previously would not have been able to do so [17].…”
Section: Potential Funding Sources For Mental Health Researchmentioning
confidence: 99%
“…6 In the absence of antiemetic prophylaxis, about 70% -80% of cancer patients receiving chemotherapy experience CINV. 7 However, proper use of antiemetic medication has the potential to improve control of CINV, maximise patients' QOL and reduce associated symptoms' management costs. 8,9 Several clinical guidelines have addressed the importance of the prophylactic administration of antiemetic drugs for preventing CINV, including the American Society of Clinical Oncology (ASCO), Multinational Association of Supportive Care in Cancer/European Society for Medical Oncology (MASCC/ESMO) and National Comprehensive Cancer Network (NCCN).…”
Section: Introductionmentioning
confidence: 99%
“…Recently also, in a randomized, double-blind, crossover study, we demonstrated conclusively that high-dose dexamethasone is more effective as an antiemetic and safer than high-dose metoclopramide in patients who are mainly receiving non-cis-platin emetogenic chemotherapy (Ibrahim et al, 1986). However, the dosages and schedule of the antiemetics used in that trial were not suitable for outpatient management.The administration of combinations of antiemetic drugs which would act at different receptor sites should improve their antiemetic potential through complete neuroreceptor blockade (Bruera et al, 1983;Krebs et al, 1985;Mason et al, 1982;Morran et al, 1979). Furthermore, combining two or more antiemetics should minimise the adverse effects produced by the constituent agents given singly in higher doses.…”
mentioning
confidence: 99%
“…The administration of combinations of antiemetic drugs which would act at different receptor sites should improve their antiemetic potential through complete neuroreceptor blockade (Bruera et al, 1983;Krebs et al, 1985;Mason et al, 1982;Morran et al, 1979). Furthermore, combining two or more antiemetics should minimise the adverse effects produced by the constituent agents given singly in higher doses.…”
mentioning
confidence: 99%
See 1 more Smart Citation